Strategia inteligentnego wspomagania biznesu w organizacji uczącej się - Dudycz, Helena (Intelligent Enterprise Strategy in the Learning Organization, 2005)
The article presents analysis of information technology of intelligent enterprise strategy for support business in the learning organization. The first part briefly characterizes the learning organization. The next part describes the four strategies (called: extension of functionality strategy, web-based enterprise strategy, active enterprise strategy and intelligent enterprise strategy) related to the new versions of ERP systems (named EERP, eERP/iERP, @ERP and IERP). The last part of the article contains of the description of information technology in realized intelligent enterprise strategy in the learning organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 203-211